CANDI SUKUH SEBAGAI TEMPAT KEGIATAN KAUM RSI - Heri Purwanto (Balai Arkeologi Yogyakarta, 2017)
A lot of studies about temple Sukuh has been conducted before, but not to the extent in which it existed as the place for kaum Rsi. Sukuh Temple is a holy place located at the slope of Lawu Mountain, away from the cities. This definitely is an absolute requirement for a holy place for kaum Rsi. Many old heritages at Candi Sukuh complex support the argument that this temple was built by the Rsis or hermits. Based on that explanation, the research questions of this study are about what factors that indicate Sukuh Temple as the place for the Rsi, and in what kind of Karsyan. The methodology used in this study was conducted in two steps; that is data collection and analysis. The data collection was including observation and literature review. The data analysis was using qualitative analysis with symbol theory. The result of this study showed that based from the old heritages it was indicated that the Karsyan of Mandala Kedewaguruan. The life of the Rsi at Sukuh Temple was related to foods and drinks. They utilized the surrounding area for farming. The harvests are eggplants, coconuts, paddies, and vegetables. In addition, in religious context, the Rsi also did some teaching and learning activities.